The Role of Knowledge Management Capabilities in Enhancing Organizational Learning and Decision-Making Quality - Gita Damayanti; Sri Hartono; Afriyani Mabruka Azzahro; Ngurah Pandji Mertha Agung Durya; Dina Destari (Malaqbi Publisher, 2026)
In an increasingly knowledge-driven and uncertain business environment, organizations are required to continuously learn and make high-quality decisions to sustain competitiveness and long-term performance. This study investigates the role of knowledge management capabilities in enhancing organizational learning and decision-making quality, with organizational learning positioned as a mediating mechanism. Using a quantitative research design, data were collected through a cross-sectional survey of employees working in knowledge-intensive organizations. The proposed research model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that knowledge management capabilities have a significant positive effect on organizational learning and decision-making quality. Furthermore, organizational learning significantly enhances decision-making quality and partially mediates the relationship between knowledge management capabilities and decision-making quality. These findings highlight that effective knowledge management not only provides direct informational support for decision making but also strengthens organizational learning processes that transform knowledge into improved decision outcomes. This study contributes to the knowledge-based view and organizational learning literature by offering an integrated framework that explains how knowledge management capabilities create value through learning and decision-making quality. From a practical perspective, the results suggest that organizations should strategically invest in both knowledge management systems and learning-oriented cultures to enhance decision effectiveness in dynamic environments.